Electoral Turnout in Chile: An Age-Period-Cohort Approach - Bargsted, Matías; Somma, Nicolás; Muñoz Rojas, Benjamín (Revista de Ciencia Política, 2019)
Through an age-period-cohort analysis applied to survey data from 1994 to 2015, we seek to understand the decline in electoral participation that has occurred in Chile during the current democratic era. Our analysis confirms some previous hypotheses, but it also illuminates some new trends. First, we find cohort effects indicating that the generations that voted during the 1988 Plebiscite tend to vote more often than those who became eligible during the democratic era. Second, Chileans’ propensity to vote increases with age, although this effect is much more pronounced among cohorts born after 1970. Finally, we find a strong and negative linear period effect, whereby the propensity to vote among all age groups has declined universally.